Prey Foraging Under Sublethal Lambda-Cyhalothrin Exposure on Pyrethroid-Susceptible and -Resistant Lady Beetles (Eriopis connexa (Coleoptera: Coccinelidae)) - D'Ávila, V. A; Reis, L. C; Barbosa, W. F; Cutler, G. C; Torres, J. B; Guedes, R. N. C (Journal of economic entomology, 2018)
Sublethal insecticide exposure may affect foraging of insects, including natural enemies, although the subject is usually neglected. The lady beetle Eriopis connexa (Germar, 1824) (Coleoptera: Coccinelidae) is an important predator of aphids with existing pyrethroid-resistant populations that are undergoing scrutiny for potential use in pest management systems characterized by frequent insecticide use. However, the potential effect of sublethal pyrethroid exposure on this predator's foraging activity has not yet been assessed and may compromise its use in biological control. Therefore, our objective was to assess the effect of sublethal lambda-cyhalothrin exposure on three components of the prey foraging activity (i.e., walking, and prey searching and handling), in both pyrethroid-susceptible and -resistant adults of E. connexa. Both lady beetle populations exhibited similar walking patterns without insecticide exposure in noncontaminated arenas, but in partially contaminated arenas walking differed between strains, such that the resistant insects exhibited greater walking activity. Behavioral avoidance expressed as repellence to lambda-cyhalothrin was not observed for either the susceptible or resistant populations of E. connexa, but the insecticide caused avoidance by means of inducing irritability in 40% of the individuals, irrespective of the strain. Insects remained in the insecticide-contaminated portion of the arena for extended periods resulting in greater exposure. Although lambda-cyhalothrin exposure did not affect prey searching by susceptible lady beetles, prey searching was extended for exposed resistant predators. In contrast, prey handling was not affected by population or by lambda-cyhalothrin exposure. Thus, sublethal exposure to the insecticide in conjunction with the insect resistance profile can affect prey foraging with pyrethroid-exposed resistant predators exhibiting longer prey searching time associated with higher walking activity reducing its predatory performance.